Problem-Based Learning (PBL): a context for collaborative learning at Aalborg University, Denmark - Mohamad Termizi Borhan,; Siti Shamsiah Sani, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study involving six first year´s Medialogy undergraduate students seeks to provide insights of the students’ perspectives on learning in a collaborative group context, learning impact and reflection associated with the participations in a Problem-Based Learning (PBL) environment.The first semester of the undergraduate studies in Aalborg University is devoted to prepare students to acquaint with PBL learning environment, especially in working collaboratively on a group project. After collecting data through interviews (at the beginning and the end of the semester) and process analysis report, the interview audio were fully transcribed to identify emerging themes and the group process analysis reports were analyzed using content analysis techniques. The results indicated that group learning process started with brainstorming ideas the tasks is divided based on both voting strategy and group member´s capability strategy. Reflecting on their learning process, students identified aspects that they need to improve including planning the timetable, enhance rapport among group members and emphasize on the quality of the discussions. In terms of the impact of PBL on student learning, students realized that they obtained skills, developed habits of peer learning and more organized learning.